2015
DOI: 10.1038/srep13423
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate Receptor 2 and 3 Mediate Bone Marrow-Derived Monocyte/Macrophage Motility in Cholestatic Liver Injury in Mice

Abstract: Sphingosine 1-phosphate (S1P)/S1P receptor (S1PR) system has been implicated in the pathological process of liver injury. This study was designed to evaluate the effects of S1P/S1PR on bone marrow-derived monocyte/macrophage (BMM) migration in mouse models of cholestatic liver injury, and identify the signaling pathway underlying this process. S1PR1–3 expression in BMM was characterized by immunofluorescence, RT-PCR and Western blot. Cell migration was determined in Boyden chambers. In vivo, the chimera mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 42 publications
5
90
0
Order By: Relevance
“…However, although BMMs are known to have unique characteristics, the roles of S1P signaling in the regulation of macrophage polarization during liver injured are poorly understood. Our preceding study has showed that blockade of S1PR 2/3 decreased liver inflammation and fibrosis by preventing BMM migration [20]. In the current study, we thus investigated the effects of S1P on BMM further, focusing on BMM polarization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, although BMMs are known to have unique characteristics, the roles of S1P signaling in the regulation of macrophage polarization during liver injured are poorly understood. Our preceding study has showed that blockade of S1PR 2/3 decreased liver inflammation and fibrosis by preventing BMM migration [20]. In the current study, we thus investigated the effects of S1P on BMM further, focusing on BMM polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that recruitment of BMMs in the injured liver could aggravate liver inflammation and thus played a crucial role in BDL-or CCl 4 -induced liver disease [20,29,30]. Among a variety of factors that mediate switch BMMs to pro-inflammatory M1 phenotype, S1P is probably one of the most potent regulatory molecules [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…48,49 A recent study has shown that sphingosine 1-phosphate receptor 2 and 3 mediate bone marrowederived monocyte recruitment in BDL mice. 50 These earlier findings suggest that not only Kupffer cells but also bone marrowederived macrophages may play key roles in liver repair…”
Section: Liver-resident and Bone Marrowederived Macrophagesmentioning
confidence: 96%